New Member of Gromochytriales (Chytridiomycetes)—Apiochytrium granulosporum nov. gen. et sp. (9th December 2018) - Karpov, Sergey A.; Moreira, David; Mamkaeva, Maria A.; Popova, Olga V.; Aleoshin, Vladimir V.; López‐García, Purificación
Abstract: Molecular phylogenetic analysis of 18S rRNA gene sequences of nearly any species of Chytridiomycota has typically challenged traditional classification and triggered taxonomic revision. This has often led to the establishment of new taxa which, normally, appears well supported by zoospore ultrastructure, which provides diagnostic characters. To construct a meaningful and comprehensive classification of Chytridiomycota, the combination of molecular phylogenies and morphological studies of traditionally defined chytrid species is needed. In this work, we have studied morphological and ultrastructural features based on light and transmission electron microscopy as well as molecular phylogenetic analysis of a parasite (strain X‐124 CCPP ZIN RAS) morphologically similar to Rhizophydium granulosporum living on the yellow‐green alga Tribonema gayanum . Phylogenetic analysis of the 18S rRNA gene sequence of this strain supports that it represents a new genus and species affiliated to the recently established order Gromochytriales . The ultrastructure of X‐124 confirms its phylogenetic position sister to Gromochytrium and serves as the basis for the description of the new genus and species Apiochytrium granulosporum . The 18S rRNA gene of A. granulosporum contains a S943 group I intron that carries a homing endonuclease pseudogene.